Violence of Religion? From Sacral to Holy - Ciancio, Claudio (Religija ir kultūra, 2014)
Among the major subjects allegedly responsible for social and political violence, there is religion. It is true that religion can promote intolerance and violence when the divine is objectified, i.e., has a form of the sacred. Without denying the symbolic dimension of religion, is necessary to purify it to access the divine in the form of the holy, the one for which it is configured as both absolutely transcendent and absolutely immanent. This thesis is illustrated here through an interpretation of the meaning of a religious feast and through the analysis of the Annunciation by Antonello da Messina.